2016
DOI: 10.1371/journal.pone.0163620
|View full text |Cite
|
Sign up to set email alerts
|

Can Sleep and Resting Behaviours Be Used as Indicators of Welfare in Shelter Dogs (Canis lupus familiaris)?

Abstract: Previous research on humans and animals suggests that the analysis of sleep patterns may reliably inform us about welfare status, but little research of this kind has been carried out for non-human animals in an applied context. This study explored the use of sleep and resting behaviour as indicators of welfare by describing the activity patterns of dogs (Canis lupus familiaris) housed in rescue shelters, and comparing their sleep patterns to other behavioural and cognitive measures of welfare. Sleep and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 47 publications
8
57
2
Order By: Relevance
“…There was no physical measurement of something believed to be linked to their welfare, such as stress hormones. Recently, Owczarczak‐Garstecka & Burman () tried to fill this gap by linking sleep directly to welfare by using signs of compromised welfare, rather than assuming a situation was stressful. Their results were counterintuitive and found that the percentage of time spent asleep during the night was not predicted by behavioural indicators of welfare.…”
Section: Discussionmentioning
confidence: 86%
“…There was no physical measurement of something believed to be linked to their welfare, such as stress hormones. Recently, Owczarczak‐Garstecka & Burman () tried to fill this gap by linking sleep directly to welfare by using signs of compromised welfare, rather than assuming a situation was stressful. Their results were counterintuitive and found that the percentage of time spent asleep during the night was not predicted by behavioural indicators of welfare.…”
Section: Discussionmentioning
confidence: 86%
“…were more active) than dogs in homes (although this may be due to home dogs being under-stimulated, so care should be taken when interpreting their lower activity as positive welfare). Another study looked specifically at sleep in dogs kennelled at rehoming centres and, although it did not find a relationship between night-time sleep and behavioural measures, it did find that dogs that spent more time resting during the day had a more positive judgement bias and exhibited fewer repetitive behaviours than dogs that did not rest as much in the daytime (Owczarczak-Garstecka et al, 2016). While this may suggest that reduced activity and increased resting during the day, may be a useful indicator of positive welfare in kennelled dogs, another study by Hiby et al (2006) found that this relationship may be more complex.…”
Section: Activity Level and Resting Behavioursmentioning
confidence: 94%
“…Temperature or previous experiences may confound. Clark et al, 1997;Stephen and Ledger, 2005;Hiby et al 2006;Kiddie and Collins, 2014 Activity/Resting May require specialised equipment Both Unclear Difficult to distinguish between rest and boredom/learned helplessness/depressive states Haley et al, 2000;Hiby et al, 2006;Rushen et al, 2012;Jones et al, 2014;Part et al, 2014;Owczarczak-Garstecka et al, 2016 Play Spontaneous play needs video recording. Elicited play relatively easy to assess.…”
Section: Easy To Assessmentioning
confidence: 99%
See 2 more Smart Citations